Surgical outcomes of the surgical techniques following management of iatrogenic trigeminal nerve injuries: A systematic review - Turki Almohammadi; Julian Yates; Marwan Aljohani; Sami Alshehri (Saudi Dental Journal)
Objective: To investigate the effectiveness of the microsurgical treatment in restoring full sensory recovery following trigeminal nerve injuries caused by iatrogenic oral and maxillofacial surgical interventions. Methods: A detailed search was conducted on the Cochrane central register of controlled trials, Medline and Embase. Clinical studies with at least twelve months of follow up were included and assessment of risks of bias was made using the Robbin I assessment tool. Results: Six studies were identified in the searches which include 227 patients. The lingual nerve was the most common injured nerve, followed by the inferior alveolar nerve. Third molar removal was the most frequent cause of nerve injury, followed by root canal treatment, pathology excision, coronectomy, orthognathic surgery, dental implants and then local anaesthetic injections. Overall, surgical interventions for nerve injuries showed neurosensory improvement postoperatively in the majority of patients. Conclusion: Direct neurorrhaphy is still the gold-standard technique when the tension at the surgical site is minimal. Promising results have been noted on conduit applications following traditional repair or grafting. Further research is needed on the efficacy of allografting and conduit applications in nerve repair.